The Effects of Changing Labor Markets and Social Policies on Income Inequality and Poverty: Hungary and the Other Visegrad Countries Compared - Michael F. Förster; István György Tóth (Luxembourg Income Study (LIS), 1998)
The transition to a market economy has lead to liberalization in a great many spheres of society in the reform economies of Central and Eastern Europe. At the same time, financial insecurity of many households persisted or increased, and certain parts of the population face for the first time risks of impoverishment. To respond to this situation and to design effective programs combating poverty under budgetary constraints is therefore one of the prime objectives of social policy in these countries. We argue in the paper that there may be two major determinants of income inequalities and poverty. First and foremost, labour and capital markets play a very important role, through the allocation of jobs and earnings opportunities to the various segments of the population. Secondly, social policies, via the redistribution of taxes through the state budget from those having higher incomes to those having lower incomes also play a role in shaping income inequalities.
Keywords: 330; Einkommensumverteilung; Arbeitsmarkt; Armut; Ungarn; Visegrad-Staaten